PLAAT1 inhibits type I interferon response via degradation of IRF3 and IRF7 in Zebrafish - Xin Zhao; Xin Zhao; Xin Zhao; Wenji Huang; Wenji Huang; Wenji Huang; Yanjie Shi; Yanjie Shi; Yanjie Shi; Jiahong Guo; Jiahong Guo; Jiahong Guo; et al. (Frontiers in Immunology, 2022)
PLAAT1 is a member of the PLAAT protein family and plays important roles in tumor suppression, transglutaminase activation and peroxisomal biogenesis. Recently, PLAAT1 has been shown to promote degradation of p53 protein and cellular organelles such as mitochondria, endoplasmic reticulum and lysosome. In this study, we show that PLAAT1 inhibits the production of type I interferon and promotes virus replication in zebrafish. Overexpression of Plaat1 in zebrafish cells suppresses antiviral responses and promotes virus replication. Mechanistically, PLAAT1 interacts with IRF3 and IRF7 to initiate degradation of IRF3 and IRF7, which can be attenuated by 3-methyladenine, an inhibitor of autophagosome. Our study provides novel insights into the functions of PLAAT1 in host immune response to viral infection.